2002
DOI: 10.1142/s0219477502000610
|View full text |Cite
|
Sign up to set email alerts
|

Resistance Noise Near to Electrical Breakdown: Steady State of Random Networks as a Function of the Bias

Abstract: A short review is presented of a recently developed computational approach which allows the study of the resistance noise over the full range of bias values, from the linear regime up to electrical breakdown. Resistance noise is described in terms of two competing processes in a random resistor network. The two processes are thermally activated and driven by an electrical bias. In the linear regime, a scaling relation has been found between the relative variance of resistance fluctuations and the average resis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
32
0

Year Published

2004
2004
2015
2015

Publication Types

Select...
4
3
1

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(33 citation statements)
references
References 54 publications
1
32
0
Order By: Relevance
“…At small λ values (high level of intrinsic disorder), we have found that the auto-correlation function displays a non-exponential (but non-power-law) decay. This behavior is different from that displayed at high λ values (low level of intrinsic disorder), where C x exhibits an exponential decay (consistent with the Lorentzian power spectrum reported in previous works [16,17,19]). Here we will focus on the case of non-exponential and non-power-law decay of correlations, a situation typical of systems which are approaching criticality, and we will show the results obtained by taking λ = 0.33 for a network of size 125 × 125, biased by a current I = 0.011 A.…”
Section: Methods and Resultssupporting
confidence: 76%
See 2 more Smart Citations
“…At small λ values (high level of intrinsic disorder), we have found that the auto-correlation function displays a non-exponential (but non-power-law) decay. This behavior is different from that displayed at high λ values (low level of intrinsic disorder), where C x exhibits an exponential decay (consistent with the Lorentzian power spectrum reported in previous works [16,17,19]). Here we will focus on the case of non-exponential and non-power-law decay of correlations, a situation typical of systems which are approaching criticality, and we will show the results obtained by taking λ = 0.33 for a network of size 125 × 125, biased by a current I = 0.011 A.…”
Section: Methods and Resultssupporting
confidence: 76%
“…When I > I B the resistor undergoes an electrical breakdown, associated with an irreversible divergence of its resistance [16,17,18,20]. For a generic value of λ this breakdown corresponds to a first order transition [17,18,19]. However, for decreasing λ values, when λ → λ min , the system becomes more and more close to its critical point [17,18,19].…”
Section: Methods and Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…7 (a) simulation results for the probability density function (PDF) of resistance fluctuations are given and qualitatively compared with theoretical distributions; Gaussian and Bramwell-Holdsworth-Pinton (BHP) distribution [18]. It is evident that for higher activation energy E D , PDF shows Gaussian-like behavior.…”
Section: Simulation Resultsmentioning
confidence: 98%
“…As a result, the power spectral density of the resistance fluctuations shows a 1/f α dependence of frequency, with α ≈ 1 for T ≤ T * . It should be also noted that the MSN model represents an extension to systems characterized by 1/f noise of a previous model existing in the literature, the stationary and biased resistor network (SBRN) model [31,32,33]. In any case, it must be underlined that, apart from the specific system described by the MSN model, the method used here for generating the time series can be also viewed as a pure numerical algorithm for generating numerical series with different and tunable correlation properties.…”
Section: Methods and Resultsmentioning
confidence: 99%